A Web-based Application for Food Recommendation - Yung Chee Kai,; Wan Hussain Wan Ishak, (Multidisciplinary Applied Research and Innovation, 2023)
People are putting greater emphasis on living a healthy lifestyle, and the food they consume is getting healthier. On the other hand, an unhealthy person needs nutrients to heal more quickly. In this study, a food recommendation system is proposed. The main goals of this project are to define the specifications for a food recommender system, create a prototype for that system, and assess how well it works. The suggested system can gather user information and provide food recommendations to the user depending on their needs. The findings of the usability study indicated that the proposed system is easy to learn. The output produced by the system was likewise well received by the respondents. Furthermore, the system can assist people, especially those who are unhealthy, in managing their food intake.